Correction: A convenient approach to an advanced intermediate toward the naturally occurring, bioactive 6-substituted 5-hydroxy-4-aryl-1H-quinolin-2-ones. Issue 12 (3rd March 2016) - Simonetti, Sebastián O.; Larghi, Enrique L.; Kaufman, Teodoro S.
Abstract : Correction for 'A convenient approach to an advanced intermediate toward the naturally occurring, bioactive 6-substituted 5-hydroxy-4-aryl-1 H -quinolin-2-ones' by Sebastián O. Simonetti, et al., Org. Biomol. Chem., 2016, DOI: 10.1039/c5ob02680f.